1997
DOI: 10.1364/ao.36.009496
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic scattering by an aggregate of spheres: far field

Abstract: In electromagnetic multisphere-scattering calculations the reexpansion method for seeking a single-field representation of the total scattered field is found impracticable because of severe numerical problems. We present a simple single-field expansion of the total scattered far field based on an asymptotic form of vector translational addition theorems. With this asymptotic expansion of the far field, we derive analytical expressions for the scattering properties of an arbitrary aggregate of spheres. Resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
135
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(141 citation statements)
references
References 23 publications
3
135
0
2
Order By: Relevance
“…The other one is the generalized Mie-solution method (GMM). GMM was developed by Xu (1995Xu ( , 1997 based on the framework of the Mie theory for a single sphere and the addition theorems for spherical vector wave functions. It provides a rigorous and complete solution to nonoverlapping multisphere light scattering problems and can be readily applied to fractal soot aggregates ( Van-Hulle et al 2002;Liu and Snelling 2008).…”
Section: Generalized Mie-solution Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other one is the generalized Mie-solution method (GMM). GMM was developed by Xu (1995Xu ( , 1997 based on the framework of the Mie theory for a single sphere and the addition theorems for spherical vector wave functions. It provides a rigorous and complete solution to nonoverlapping multisphere light scattering problems and can be readily applied to fractal soot aggregates ( Van-Hulle et al 2002;Liu and Snelling 2008).…”
Section: Generalized Mie-solution Methodsmentioning
confidence: 99%
“…Execution of this numerically exact method requires the positions, diameter, and refractive index of each constituent sphere (primary particle). Although CTM has become the most popular method to study the radiative properties of various scatterers , GMM has also been demonstrated to be a powerful tool to study radiative properties of various particles (Xu 1995(Xu , 1997Van-Hulle et al 2002;Liu and Snelling 2008). In fact, CTM and GMM share a very similar theoretical framework, though differences exist (Xu and Khlebtsov 2003).…”
Section: Generalized Mie-solution Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been successfully applied to compute the scattering properties of single core-mantle spheres (Hong et al 2008). Xu (1995Xu ( , 1996Xu ( , 1997 and Xu and Gustafson (2001) continued the development to produce what is known as the GMM method to deal with aggregates of arbitrary size and configuration, formed from monomers that are homogeneous spheres of possibly different radii and compositions. This GMM method was recently used to calculate the singlescattering properties of fractal aggregates by Van-Hulle et al (2002), Liu and Smallwood (2010, 2011), and Li et al (2010.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2. We used the rigorous solution for scattering by an aggregate of spheres [Xu, 1995[Xu, , 1997] that has been thoroughly tested at the University of Florida microwave scattering facility and shown to be accurate [Xu and Gustafson, 1997;1999 As stated in KMGG, the search area of the Fence was divided into two regions, 1000-3000 km altitude and 3000-20,000 km altitude, in order to accommodate different published values for the altitude of cometary breakup. For the high altitude range, after allowing for the vast increase in search area above 3000 km and the change in sensitivity of the Fence with range, KMGG found the small comet detection rate to be comparable for both altitude regimes.…”
Section: Introductionmentioning
confidence: 99%